Harm minimisation for self-harm: a cross-sectional survey of British clinicians’ perspectives and practices - Alexandra Pitman; Nicola Morant; Faraz Mughal; Sarah L Rowe; Aishah Madinah Haris; Evelina Bakanaite (BMJ Open)
Objective Harm minimisation for self-harm is an alternative to preventive strategies and focuses on maximising safety when self-harming. We explored the views of clinicians on harm minimisation for self-harm to describe reported use and acceptability in clinical practice.Design A cross-sectional study using an online survey consisting of fixed-choice and open-ended questions.Setting Primary and secondary care practices in England, Scotland and Wales.Participants Snowball sampling of UK-based clinicians (n=90; 67% female) working with people who self-harm and who have or have not previously recommended harm minimisation methods to patients.Results Of the 90 clinicians sampled, 76 (84%) reported having recommended harm minimisation techniques to people in their care who self-harm. Commonly recommended techniques were snapping rubber bands on one’s wrist and squeezing ice. Other techniques, such as teaching use of clean instruments when self-harming, were less likely to be recommended. Perceived client benefits included harm reduction and promotion of the therapeutic relationship. Perceived potential limitations of a harm minimisation approach for self-harm were (a) potential worsening of self-harm outcomes; (b) ethical reservations; (c) doubts about its effectiveness and appropriateness; and (d) lack of training and clear policies within the workplace.Conclusions In our sample of UK-based clinicians in various settings, harm minimisation for self-harm was broadly recommended for clients who self-harm due to perceived client benefits. However, future policies on harm minimisation must address clinicians’ perceived needs for training, well-defined guidelines, and clear evidence of effectiveness and safety to mitigate some clinician concerns about the potential for further harm.